1999
DOI: 10.1097/00003072-199905000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Tc-99m Citrate Scintigraphy in the Evaluation of Palpable Breast Masses

Abstract: The aim of this study was to evaluate the potential of Tc-99m citrate as a new tumor-localizing agent in palpable breast masses. Scintimammography was performed in 43 female patients. Of these, 10 women (group A) were considered to be healthy with no palpable breast masses, and the remaining 33 patients (group B) had palpable breast masses. All patients with palpable breast masses underwent fine-needle aspiration cytology and subsequent biopsy within 2 weeks of the study. Nine patients had a primary malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For assessing primary lesions, it is sometimes possible with PET to detect tumors that are missed by mammography and other standard methods. Several PET and SPECT radiotracers have been evaluated as breast tumor imaging agents in pre-clinical and clinical studies [13,49,53,56,57,63,255,[277][278][279][280][281][282][283][284][285][286][287][288][289][290][291]. The potential PET tracers for breast cancer include [ 11 C]methionine [292], [ 11 C]tyrosine [288,293], [ 18 F]fluoroestradiol and radiolabeled progestins [287,294] are examples of tracers in preliminary stages of evaluation.…”
Section: G Sigma Receptors In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…For assessing primary lesions, it is sometimes possible with PET to detect tumors that are missed by mammography and other standard methods. Several PET and SPECT radiotracers have been evaluated as breast tumor imaging agents in pre-clinical and clinical studies [13,49,53,56,57,63,255,[277][278][279][280][281][282][283][284][285][286][287][288][289][290][291]. The potential PET tracers for breast cancer include [ 11 C]methionine [292], [ 11 C]tyrosine [288,293], [ 18 F]fluoroestradiol and radiolabeled progestins [287,294] are examples of tracers in preliminary stages of evaluation.…”
Section: G Sigma Receptors In Oncologymentioning
confidence: 99%
“…The potential PET tracers for breast cancer include [ 11 C]methionine [292], [ 11 C]tyrosine [288,293], [ 18 F]fluoroestradiol and radiolabeled progestins [287,294] are examples of tracers in preliminary stages of evaluation. Other types of tracers are in various stages of development and testing [13,49,53,57,283,284,291,295]. At this time, no agent has proven to be sufficiently accurate and specific in a clinical trial to be confirmed as a useful clinical tool.…”
Section: G Sigma Receptors In Oncologymentioning
confidence: 99%
“…Recently a new diagnostic method called scintimammography has been developed, which is performed with a scintillation camera and tumour-seeking radiopharmaceuticals such as 99m Tc sestamibi, 99m Tc methylene diphosphonate or 99m Tc tetrofosmin (Prats et al 1999, Melloul et al 1999, Mondal et al 1999, Arslan et al 1999, Danielsson et al 1999, Howarth et al 1999, Horne et al 1999. The diagnostic accuracy of this method for detecting breast cancer has been demonstrated to have a high sensitivity and specificity of around 83-97% and 74-88% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroadenomas include histological variants that exhibit distinct histological features and variations in their clinicopathological features, including cellular, juvenile, and complex fibroadenomas. Various radiopharmaceuticals have been reported to show varying degrees of uptake in fibroadenoma 1–4 . 68 Ga-FAPI PET/CT has been positive in many primary breast malignancies and may also be positive in many nonmalignant lesions or diseases 5–12 .…”
mentioning
confidence: 99%